Influence of Non-incineration System on Soil Carbon/Nitrogen Ratio Values of Yakonde (Y2) Series under Cassava Cultivation in Yangambi, D.R. Congo - Kombele M; Motondo M; Motosia A; Kolela B; Ugencan D; Lifafu H; Kombele F; Kakuni J; Kombele FM (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
The objective pursued in this research was to assess the potential of cassava cultivation in the non-incineration of cut plant biomass in the management of the stock of organic carbon and its main component in the soil, namely its C/N ratio. . To do this, five cassava cultivars have been introduced including: Obama, M'vuazi, Disanka, Zizila and Sansi. These five cultivars were planted in forest fallow in plots each measuring 0.48ha and repeated four times on the Yakonde series (Y2) on the Isalowe plateau in Yangambi. These plots were developed in non-incineration of biomass and from where 108 disturbed soil samples were taken in two groups, one of 54 samples at one month and the other of 54 samples at six months. culture in soil slices 0-20 and 20-40cm deep. These 108 samples made it possible to evaluate the stock of organic matter (M.O.S), total organic carbon (TOC), total organic nitrogen of the soil in order to determine the values of the carbon/nitrogen ratio at one and six months of age of cultivation of five varieties of cassava. M.O.S under the varieties Disanka (21.2±1.0%), Obama (19.6±0.7%) and Sansi (19.5±2.1%) at six months of age in the 0 range -20cm. While under Obama and Disanka, they were lower and respectively 6.1±1.3% and 7.0±2.9% in the 0-20cm age group at one month. The highest average soil TOC values were observed at six months of age under the Disanka (12.3±0.6%), Obama (11.6±0.7%) and Sansi (11. 3±1.3%) in the 0-20cm range; while the weakest were at one month of age under the varieties Obama (3.5 ± 0.8%) and M'vuazi (4.1 ± 1.7%) in the 20-40cm range. The average values of soil Nt contents which vary from 0.4±0.0 to 1.0±0.0% at the surface and from 0.4±0.1 to 0.9±0.4% at depth under the five varieties of cassava were found to be numerically superior to those of the soil under the old secondary forest in the two slices of soil studied (respectively by 0.5±0.1% and 0.2±0.1%). For the two slices of soil studied, the highest values in Nt of the soil (0.9±0.1% and 1.0±0.0% for the slice of 020cm; 0.9±0.4% and 0.9±0.1% for the 20-40cm slice) are observed at six months of age respectively under the Sansi and Disanka varieties. As for the C/N ratio, it decreases with the depth of the soil, except for the Zizila and Disanka varieties at one month of age. The highest mean values are observed under Sansi (12.4±2.8) at one month of age and under Disanka (12.3±0.3) at six months of age in the 0-20cm range; the weakest are under Obama (7.7±7) at one month and under Zizila (7.5±0.6) at six months of age in the 20-40cm range. In fact, the highest mean value of the C/N ratio remains that of the control forest taken as the reference forest.